2005
DOI: 10.1167/iovs.04-1104
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Contraction and Metamorphopsia Scores in Eyes with Idiopathic Epiretinal Membrane

Abstract: Metamorphopsia scores correlate well with measurements of retinal contraction due to idiopathic ERM. Using M-CHARTS is a simple and useful method for quantitatively monitoring metamorphopsia in patients with ERM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
70
0
11

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(95 citation statements)
references
References 9 publications
8
70
0
11
Order By: Relevance
“…Although the number of the subjects in this study was small, our current results could substantiate the previous found about relationships between the directions of retinal contraction and metamorphopsia. 7 It is widely known that ERM frequently associates with posterior vitreous detachment (PVD). Kishi et al 15 have postulated that in cases of ERM with or without PVD, the thin premacular vitreous cortex that forms the posterior wall of the premacular liquefied pocket has a key role in the development of ERM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the number of the subjects in this study was small, our current results could substantiate the previous found about relationships between the directions of retinal contraction and metamorphopsia. 7 It is widely known that ERM frequently associates with posterior vitreous detachment (PVD). Kishi et al 15 have postulated that in cases of ERM with or without PVD, the thin premacular vitreous cortex that forms the posterior wall of the premacular liquefied pocket has a key role in the development of ERM.…”
Section: Discussionmentioning
confidence: 99%
“…Details of the application and procedure for the use of this software were described elsewhere. 7 Briefly, the comparison image taken after the spontaneous separation of ERM was superimposed on the baseline image taken before the membrane separation so that the optic disc and choroidal vessels matched. The distance between the center of the optic disc and the fovea was calibrated to be 151 (4.02 mm), and the macular area within 201 was divided into 25 areas.…”
Section: Quantification Of Retinal Contractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Известно, что основной причиной М у пациен-тов с патологией макулярной зоны является нарушение архитектоники фоторецепторов сетчатки. В случае с иЭРМ нарушение физиологического расположения фо-торецепторов и/или их наружных сегментов происходит за счет тракционного воздействия эпиретинальной ткани [4]. Использование новых технологий визуализации сет-чатки позволяет выявить новые возможные патогенетиче-ские основы симптомов заболеваний, в частности М. Применение адаптивной оптики в приборах позволяет устранить аберрации высокого порядка и значительно по-высить их разрешение, благодаря чему появляется воз-можность оценить in vivo состояние различных слоев сет-чатки.…”
Section: обзоры литературыunclassified
“…Угол зрения, при котором пун-ктирная линия стала восприниматься как прямая, являет-ся мерой выраженности М. Использование метода позво-ляет количественно оценить выраженность М как в вер-тикальном, так и в горизонтальном направлении. Ис-пользование различных методов легло в основу несколь-ких исследований количественных и качественных харак-теристик М у пациентов с иЭРМ [4,8,9]. В исследовании С. Matsumoto и соавт.…”
Section: обзоры литературыunclassified